2019
DOI: 10.1093/toxsci/kfz084
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Induced Upregulation of MicroRNAs Directs the Suppression of Endothelial LRP1 in Alzheimer’s Disease Model

Abstract: Chronic exposure to copper and its dyshomeostasis have been linked to accelerated cognitive decline and potentially increasing risk for Alzheimer's disease (AD). We and others have previously demonstrated that exposure to copper through drinking water significantly increased parenchymal amyloid-beta (Ab) plaques and decreased endothelial low-density lipoprotein receptor-related protein 1 (LRP1) in mouse models of AD. In this study, we determined the underlying mechanisms that microRNA critically mediated the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 73 publications
(94 reference statements)
1
19
0
Order By: Relevance
“…Notably, non-ceruloplasmin Cu crosses the BBB, which is exemplified by Wilson disease, the paradigmatic disorder of Cu accumulation on a monogenic basis. In AD, as well, its excess can lead to impairment in the hippocampal synaptic structure and spatial memory, as shown in preclinical studies and confirmed in AD brain specimens [ 90 , 96 , 97 ].…”
Section: Main Processes Of Oxidative Stress In Ad: the Linkage With Cu Imbalancementioning
confidence: 93%
See 2 more Smart Citations
“…Notably, non-ceruloplasmin Cu crosses the BBB, which is exemplified by Wilson disease, the paradigmatic disorder of Cu accumulation on a monogenic basis. In AD, as well, its excess can lead to impairment in the hippocampal synaptic structure and spatial memory, as shown in preclinical studies and confirmed in AD brain specimens [ 90 , 96 , 97 ].…”
Section: Main Processes Of Oxidative Stress In Ad: the Linkage With Cu Imbalancementioning
confidence: 93%
“…This hypothesis stems from the increasing number of experimental, meta-analysis, and multifactorial studies that have delineated that chronic exposure to Cu and its imbalance is linked to accelerated cognitive decline and AD pathology in the human brain [ 79 , 85 , 86 , 87 , 88 ]. As evidenced by seminal dietary experiments [ 89 ] and confirmed in AD transgenic models [ 90 , 91 , 92 ], a paradigm of 9–12 months of exposure to 1.3 ppm Cu in drinking water unraveled the mechanism of Cu toxicity linked to AD pathology. Chronic Cu exposure (1.3 ppm Cu in drinking water) after 9 months interferes with the LRP1-mediated clearance of Aβ alterations in cortical vasculature by altering microRNA dynamics, which indicates an involvement of Cu exposure in brain vascular damage by augmenting vascular Aβ accumulation and, thereby, increasing the risk for developing cognitive decline and AD [ 90 ].…”
Section: Main Processes Of Oxidative Stress In Ad: the Linkage With Cu Imbalancementioning
confidence: 99%
See 1 more Smart Citation
“…Non-ceruloplasmin Cu fits well in this construct since it is a loosely bound specie of Cu in general circulation and has been demonstrated to be a potential prognostic biomarker for conversion from mild cognitive impairment (MCI) to symptomatic AD, typified by copper imbalance ( Squitti et al, 2014 ; Rozzini et al, 2018 ; Sensi et al, 2018 ). In AD, non-ceruloplasmin Cu reaches values similar to Wilson disease ( Squitti et al, 2018 ) and has demonstrated a fair sensitivity in detecting which individuals with MCI will convert to Cu-AD ( Squitti et al, 2014 ) and high specificity (95%) in detecting patients affected with Cu-AD due to copper exposure ( Squitti et al, 2017 ), in line with preclinical models of the disease ( Sparks and Schreurs, 2003 ; Singh et al, 2013 ; Yu et al, 2018 ; Hsu et al, 2019 ). Recently, several studies have shown that non-ceruloplasmin Cu might serve as a stratification biomarker for a subset of AD patients ( Kepp and Squitti, 2019 ).…”
Section: Essential Trace Metals: Diagnostic Perspectives In Ad and Amdmentioning
confidence: 99%
“…However, when not properly bound, Cu undergoes redox cycling reactions with O 2 , resulting in the catalytic production of reactive oxygen species (ROS) of which H 2 O 2 can diffuse through cell membrane and then produce the very reactive hydroxyl radical (HO•), catalyzed by Cu (Fenton-type reactions) [11]. In the past decade, many studies have uncovered a link between AD pathogenesis and Cu dysmetabolism (reviewed in [12]): AβPP/Aβ are Cu binding proteins with a potential role as natural Cu buffering proteins, and Cu 2+ binding dramatically changes Aβ aggregation propensity, structure, and toxicity [13], with a plethora of effects spanning from reducing energy production in mitochondria to altering synaptic function and cognitive deterioration (reviewed in [12]), as revealed by preclinical models of chronic Cu exposure [14][15][16][17]. Furthermore, mutations in the genes involved in Aβ buildup and processing (AβPP, PSEN1/PSEN2) have been reported to disturb the metal-buffering AβPP/Aβ system [12].…”
Section: Introductionmentioning
confidence: 99%